Between Pricing and Investment, What Mobility Policies Would Be Advantageous for Île-de-France? - Fabien Leurent; Sheng Li (Journal of Advanced Transportation)
This article provides a prospective study of mobility policies for the private car and public transit (PT) modes of transportation in the Paris Ile-de-France region. Different economic instruments are considered: pricing of car traffic or transit service, subsidizing PT, and investment in PT  to improve service quality. Policy scenarios are defined and assessed according to multiple criteria: users’ benefits, PT  production costs and fare revenues, public subsidies, and environmental damage both local (air pollution) and global (carbon emissions). The social, economic, and environmental impacts are monetized and aggregated in a wellbeing function. While a first set of scenarios are specified directly, two other sets of scenarios are calculated by optimizing the wellbeing function with respect to action variables on the transit mode in the medium or long run. The regional mobility system is modeled in a structural way: concentric subregions, travel demand segmented by geographical and behavioral conditions, environmental impacts based on road and rail traffic, and car mode and transit mode depicted each as a set of technical components involving 1 to 3 structural factors that can make action levers. This model-based methodology allows for trading between different kinds of impacts and identifying performance-oriented policy packages.